Case report: Accidental aconitine poisoning caused by the inappropriate use of a type of Chinese patent medicine - Shang, Ruikai; Liu, Hongyu; Tian, Qiaoxin; Liu, Yuru; Jian, Xiangdong; Li, Qilu (Frontiers in Pharmacology, 2025)
BackgroundCompound schizonepeta fumigation lotion is a type of Chinese patent medicine for external use. It has the effect of dispelling wind, eliminating dampness, reducing swelling, and relieving pain. Clinically, it is used for anal fumigation and treatment of external hemorrhoids, anal fissures, and other diseases. Aconitum species are widely used in the field of traditional Chinese medicine. However, improper use and overdose can easily cause acute poisoning, leading to malignant arrhythmias, cardiogenic shock, and even death.MethodsThis study retrospectively analyzed the clinical data of eight patients who were treated in our hospital from June 2023 to February 2024 after taking compound schizonepeta fumigation lotion by mistake.Case presentationWe report 8 cases of patients who took compound schizonepeta fumigation lotion by mistake. Most patients were illiterate and older, and poisoning was attributed to the misuse of an external drug. The affected patients exhibited different degrees of arrhythmia, with 2 receiving tracheal intubation, assisted ventilation, and hemoperfusion. Finally, all patients were clinically cured and subsequently discharged.ConclusionA considerable number of accidental aconitine poisoning cases were reported over a short period, alerting clinicians to their growing incidence. Meanwhile, when prescribing medications, clinicians must provide clear instructions on proper usage and ensure that patients strictly adhere to the dosage and administration guidelines outlined in the drug instructions. Additionally, patients should be informed that any errors in medication administration require urgent medical attention. Health professionals should aim to improve public understanding of safe medication practices, promote health literacy.